The Role of the Low-Density Lipoprotein Receptor-Related Protein (LRP) in the Plasma Clearance and Liver Uptake of Recombinant Single-chain Urokinase-type Plasminogen Activator in Rats - van der Kaaden, Marieke E; Rijken, Dingeman C; Kar Kruijt, J; van Berkel, Theo J C; Kuiper, Johan (Thrombosis and Haemostasis, 1997)
Urokinase-type plasminogen activator (u-PA) is used as a thrombolytic agent in the treatment of acute myocardial infarction. In vitro, recombinant single-chain u-PA (rscu-PA) expressed in E.coli is recognized by the Low-Density Lipoprotein Receptor-related Protein (LRP) on rat parenchymal liver cells. In this study we investigated the role of LRP in the liver uptake and plasma clearance of rscu-PA in rats. A preinjection of the LRP inhibitor GST-RAP reduced the maximal liver uptake of 125I-rscu-PA at 5 min after injection from 50 to 30% of the injected dose and decreased the clearance of rscu-PA from 2.37 ml/min to 1.58 ml/min. Parenchymal, Kupffer and endothelial cells were responsible for 40, 50 and 10% of the liver uptake, respectively. The reduction in liver uptake of rscu-PA by the preinjection of GST-RAP was caused by a 91 % and 62% reduction in the uptake by parenchymal and Kupffer cells, respectively. In order to investigate the part of rscu-PA that accounted for the interaction with LRP, experiments were performed with a mutant of rscu-PA lacking residues 11-135 (= deltal25- rscu-PA). Deletion of residues 11-135 resulted in a 80% reduction in liver uptake and a 2.4 times slower clearance (0.97 ml/min). The parenchymal, Kupffer and endothelial cells were responsible for respectively 60, 33 and 7% of the liver uptake of 125I-deltal25-rscu-PA. Preinjection of GST-RAP completely reduced the liver uptake of delta 125-rscu-PA and reduced its clearance to 0.79 ml/min. Treatment of isolated Kupffer cells with PI-PLC reduced the binding of rscu-PA by 40%, suggesting the involvement of the urokinase-type Plasminogen Activator Receptor (u-PAR) in the recognition of rscu-PA. Our results demonstrate that in vivo LRP is responsible for more than 90% of the parenchymal liver cell mediated uptake of rscu-PA and for 60% of the Kupffer cell interaction. It is also suggested that u-PAR is involved in the Kupffer cell recognition of rscu-PA.